Penerapan E-Office Dalam Administrasi Perkantoran - Oktaf Juairiyah; Hendrixon Hendrixon (Badan Penelitian and Pengembangan (Balitbang), Padang, West Sumatra, Indonesia, 2017)
Growth of E-Government (e-Gov) in Indonesia still lags far behind other countries. Based EGDI, E-Government Development Index, Indonesia ranked 7th in the Southeast Asian region. Utilization of e-Gov is still underdeveloped because of the culture and behavior of public servants. Balitbangda as an institution of Development & Innovation has developed organization's internal electronic office online which facilitates the disposition of the administration office employees especially incoming mail, so mail can be processed more quickly and efficiently.